Line intensity parameters, He-broadening and line shift coefficients in the 2v20 and 3v21 − v21 bands of OCS. (19th March 2022) - Dridi, N.; Jellali, C.; Hmida, F.; Hui, L.; Kwabia Tchana, F.; Landsheere, X.; Hammami, K.; Rotger, M.; Aroui, H.
Abstract : Using Fourier transform spectrometer, He-broadening coefficients in the 2 v 2 0 and 3 v 2 1 − v 2 1 bands of carbonyl sulfide ( 16 O 12 C 32 S) have been measured for the first time in the P- and R -branches. Measurements have been performed at room temperature (295 K) for 200 ro-vibrational lines with rotational quantum number ranging from 1 ≤  J  ≤ 64, using a mono-spectrum non-linear least squares fitting of Voigt profiles. The measured values were discussed as a function of the rotational quantum number and compared to previous data. These broadening coefficients were also calculated on the basis of Robert and Bonamy's formalism using an ab-initio potential energy surface (PES). In addition, we have measured pressure shift coefficients for 92 transitions in both bands, these results were compared with those of the 2ν3 band. The line intensities in the 2 v 2 0 and 3 v 2 1 − v 2 1 bands were also retrieved using the same spectra. The analysis of these intensities allows us to derive a consistent set of line intensity parameters such as vibrational transition moments, band intensities as well as Herman-Wallis (HW) coefficients. GRAPHICAL ABSTRACT: UF0001